Bio-Psychosocial Impact on the Development of Depression in Adolescents - Chukwuere, Precious Chibuike (International Journal of Criminology and Sociology, 2021)
Depression is a complex and multi-layered mental health disorder, which leads to a loss of interest in the person’s usual daily life activities with apparent low moods that last for an extended period and feelings of hopelessness. Depression is prevalent among all age groups, including adolescents, with devastating consequences that pose a public health concern. This paper analyzed the bio-psychosocial impacts on the development of depression in adolescents. The paper demonstrated that the onset of depression in adolescents is facilitated by bio-psychosocial factors of a biological, psychological, and social nature. Taking cognizance of the vulnerable nature of the adolescent developmental stage, this paper gave an expository explanation of the bio-psychosocial factors affecting the development of depression in adolescents. Proper understanding of and identifying the bio-psychosocial factors promulgating depression in adolescents underscores the need for propounding protective factors that could facilitate adequate prevention and intervention to mitigate the development of depression in adolescents.